The impact of digital economy development on public health: evidence from Chinese cities - Li, Hao; Li, Yu (Frontiers in Public Health, 2024)
Introduction The swift advancement of the digital economy not only plays a crucial role in stimulating a country’s economic growth but also exerts a significant influence on national health and well-being. Methods Adopts the data of 285 prefecture-level cities in China from 2010 to 2022, and employs the panel data fixed-effects model, spatial Durbin model, and mediated effects model to study the impact of digital economic development on the level of urban public health. Results It is found that digital economic development significantly improves the level of urban public health, and the effect has a spatial spillover effect. The impact of digital economic development on urban public health is mainly concentrated in cities with higher levels of economic development, higher levels of digital economic development, and lower levels of urban public health. Among them, technological innovation and information dissemination are the main dissemination channels through which digital economic development affects the level of urban public health. Discussion The advancement of the digital economy significantly impacts urban public health. It is advisable to bolster policies guiding digital economy development, enhance cross-sector collaboration between the digital economy and public health, reinforce public health education and awareness campaigns, improve the digital health literacy of the population, continue to enhance the fairness and accessibility of basic medical services, and address and bridge the “digital divide” between regions, as well as urban and rural areas.